When Death Meets AI: Engaging in New Death Ways in Portugal - Saraiva, Clara (Religions (Basel, Switzerland ), 2025)
This paper explores death practices and how societies have “placed the dead”. It examines the implications of analyzing death in the digital age, using Portugal as a case study. In a country where death has long been tied to Catholic traditions, how do people respond to rising cremation rates, online memorials, and social media groups dedicated to the deceased? Are they open to “digital death ways”, such as AI-driven chatbots, holograms, and platforms that preserve messages beyond one’s lifetime? Following Recuber’s call for empirical studies on how, when, and by whom technology is used to communicate with the dead, this research serves as a preliminary step toward a broader project on Portuguese digital death practices. It focuses on two key themes: changes in the treatment of physical remains due to evolving perceptions of the deceased and the relationships between the living and the dead (also in the new form of digitally resurrected personas).